Impact of electronic medical records system on the management of patients' records. - Lim, Edmund Chee Siang. (2008)
In healthcare organizations, Electronic Medical Record (EMR) system is being used to capture, organize, maintain and retrieve patient’s medical records. The purpose of this study is to find out the impact of EMR system on the management of patients’ records and services provided by the Singapore General Hospital (SGH).